UPOU open educational resources (OERs) [electronic resource] (University of the Philippines Open University, 2020)
The UPOU Commons under this link is the repository of Open Educational Resources (OERs) developed by the UP Open University. These OERs also include video materials and Study Guides developed for Business Analytics major track of IT Education and Business Management Programs as well as the Service Management Program based on relevant PSGs issued by CHED. The materials are licensed under CC-BY-NC-ND.